PENGARUH INTEGRATED COASTAL MANAGEMENT (ICM) TERHADAP PERLINDUNGAN WILAYAH PESISIR DI NEGARA ASIA TIMUR - Kholik, Saeful; Siregar, Syamsul Bahri; Attoilah, Attoilah; Alam, Kodrat; Jastitia, Mentari (Yustitia, 2024)
Integrated coastal management (ICM) is a guideline and framework for peer assessment services for coastal area protection and management. The ratification of the international conference on the protection of seas and coastal areas underlies the exploitation of seas and coastal areas that exceed the carrying capacity and resilience of environmental management. The conception of ICM in its framework carries integration or integration between sectors such as central and local governments, the private sector, and entrepreneurs. The success of the conception of ICM can be seen in terms of the functions and rules of ICM that affect the development of sustainable coastal areas. However, with the success of ICM, of course, it saves the negative side of the limits and policy patterns based on local government authority, it will be possible to overlap the determination of the role and function of centralized ICM. The research method used is juridical-normative, namely research that prioritizes data analysis based on norms and rules that can then be analyzed through qualitative stages with description-analysis. Based on the results of the study that the limits of the function and role of ICM lie in matters of authority between the central and regional governments, these limits will arise on the content of the interests of managing arrangements, utilizing coastal areas.